Stand growth scenarios for Bombacopsis quinata plantations in Costa Rica - Pérez Cordero, L.D.; Kanninen, M.; Ugalde Arias, Luis A. (2003)
In total 60 plots of approximately 80 trees each (including missing trees) were measured, with ages between 1 and 26 years. The main objective of this study was to develop intensive management scenarios for B. quinata plantations in Costa Rica to ensure high yielding of timber wood. The scenarios were based on a fitted curve for the relationship of DBH, and total height with age. A criterion of maximum basal area (18, 20, 22 and 24 m2 ha-1) was used to simulate different site qualities. Plantation density was modeled as a function of the crown area occupation of the standing trees. The scenarios consist of rotation periods between 23 and 30 years, final densities of 100–120 trees ha-1, mean DBH between 46 and 56 cm, and mean total heights of 30–35 m. The productivity at the end of the rotation varies between 9.6 and 11.3 m3 ha-1 per year, yielding a total volume at the end of the rotation of 220–340 m3 ha-1. The scenarios presented here may provide farmers and private companies with useful and realistic growth projections for B. quinata plantations in Costa Rica.